1998
DOI: 10.1021/ja9826237
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous p-Type Silicon Fabry−Perot Layers. Fabrication, Characterization, and Applications in Biosensing

Abstract: We present in this paper that porous silicon can be used as a large surface area matrix as well as the transducer of biomolecular interactions. We report the fabrication of heavily doped p-type porous silicon with pore diameters that can be tuned, depending on the etching condition, from approximately 5 to 1200 nm. The structure and porosity of the matrixes were characterized by scanning force microscopy (SFM) and scanning electron microscopy (SEM), Brunnauer-Emmett-Teller nitrogen adsorption isotherms, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
349
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 379 publications
(367 citation statements)
references
References 41 publications
11
349
0
1
Order By: Relevance
“…The non-linear nature of the gradient could be attributed to the non-linear decrease in current density across the substrate. Previous studies have observed similar results 24,25 . Several HF/ethanol ratios were also investigated and it was found that increasing the concentration of HF led to a steeper decline in the pore size along the gradient.…”
Section: Preparation Of Porous Silicon Gradientssupporting
confidence: 78%
“…The non-linear nature of the gradient could be attributed to the non-linear decrease in current density across the substrate. Previous studies have observed similar results 24,25 . Several HF/ethanol ratios were also investigated and it was found that increasing the concentration of HF led to a steeper decline in the pore size along the gradient.…”
Section: Preparation Of Porous Silicon Gradientssupporting
confidence: 78%
“…These results are in accordance with earlier work, in which an approximately exponential dependence of the pore diameter on the current density was found for highly-doped p-type samples. 4 The porous Si double-layer, produced by applying the "single-layer 1" etching conditions followed immediately by the "single-layer 2" conditions, possesses a combination of the two single layers one on top of the other. The SEM image (Fig.…”
Section: Determination Of Porosity and Thickness Of Porous Si Layersmentioning
confidence: 99%
“…2 represent the index contrast at each of the interfaces a, b, or c (see Fig. 1): (4) Where n air , n 1 , n 2 , and n Si represent the refractive index of air (or of the solution), layer 1, layer 2, and bulk Si, respectively. The quantities n 1 and n 2 represent the total refractive index of the layer and everything it contains (silicon, SiO 2 , solution, air, biomolecule, etc.).…”
Section: Interpretation Of Interferometric Reflectance Spectramentioning
confidence: 99%
“…11 The electronic or optical properties of porous silicon can also be used as the transducer of biomolecular interactions, thus qualifying its utility in biosensor applications. 12,13 The devices fabricated with PSi have shown promise, owing to the ease of fabricating one-dimensional photonic crystals. 14 A significant benefit of biosensing with PSi photonic crystals is the labelfree transduction by optical interference ͑change in refractive index n within the film͒.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Unfortunately, the instability of the underlying surface to aqueous environments has hindered the wide-scale employment of PSi for biological applications. 17,18 Recent interest in PSi was focused on its use as a delivery vehicle for therapeutic agents such as ibuprofen 19 and insulin. 20 Central to the use of PSi as an effective drug delivery system is the need to find balance between passivation of the highly reactive native Si-H x surface species to minimize damage to the loaded molecule and control the release of the drug by erosion of the PSi matrix.…”
Section: Introductionmentioning
confidence: 99%